EVALUATING INSULIN RESISTANCE IN CHILDREN: A CRITICAL APPRAISAL OF MINIMAL MODELS - Corina Pienar; Ramona Stroescu; Adela Chirita-Emandi; Andreea Dobrescu; Maria Puiu (Amaltea Medical Publishing House, 2014)
Childhood obesity has followed, during the last two decades, an ascending trend. Insulin resistance (IR) is central to the pathophysiology of obesity. So far, several methods of assessing IR have been proposed. We aimed to evaluate critically some of the simplest methods used to assess IR in the pediatric population. We studied retrospectively the records of children evaluated for obesity in the "Louis Ţurcanu" Emergency Hospital for Children Timişoara, over a period of 10 years. The study population consisted of 342 children. Anthropometric and metabolic variables were analyzed, and the following indices of IR were assessed: impaired glucose tolerance (IGT), Homeostatic Model of Assesment-IR (HOMA-IR), Homeostatic Model of Assesment- b (HOMAβ), Quantitative Insulin Sensitivity Check Index (QUICKI) as well as the TG/HDLc ratio. Data was expresed as frequencies, means ± standard deviations or median ± interquartile interval for or a 95% confi dence interval. The t-test for independent groups or the Mann-Whitney test to assess differences of IR indices across weight, gender and pubertal categories. HOMA-IR diagnosed the most children with IR, at the opposite pole we found QUICKI. IGT was a rare fi nding. It is necessary to reconsider how we assess the carbohydrate metabolism in children. Of the methods we evaluated, HOMA-IR is the optimal method for assessing IR children.